2017
DOI: 10.1186/s12860-017-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Coral cell separation and isolation by fluorescence-activated cell sorting (FACS)

Abstract: BackgroundGeneralized methods for understanding the cell biology of non-model species are quite rare, yet very much needed. In order to address this issue, we have modified a technique traditionally used in the biomedical field for ecological and evolutionary research. Fluorescent activated cell sorting (FACS) is often used for sorting and identifying cell populations. In this study, we developed a method to identify and isolate different cell populations in corals and other cnidarians.MethodsUsing fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…Cnidarians, and in particular scleractinian corals, are also critically important for ocean biodiversity and health 8 , 9 . However, much about the cell biology of anthozoans is still unknown 10 , 11 , in part due to there being no reliable cell culture method established 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Cnidarians, and in particular scleractinian corals, are also critically important for ocean biodiversity and health 8 , 9 . However, much about the cell biology of anthozoans is still unknown 10 , 11 , in part due to there being no reliable cell culture method established 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Eight polyps (about 10 8 cells) were fixed with 4% paraformaldehyde (PFA) overnight. After washing twice with 3.3× PBS 38 and dissociating the tissue in 2 ml 3.3× PBS using a 7-ml glass Dounce tissue grinder (Wheaton), another 3 ml 3.3× PBS was added. The mixture was then transferred to a 15-ml conical tube and centrifuged at 1,000 g for 3 min (Sorvall Lynx 6000 centrifuge, ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Microfluidics is a simple, low-cost, and easy-to-operate technology compared with traditional macroscale technology that requires large-scale operation equipment and a suitable laboratory facility. The principle of separation in microfluidic systems operates via well-designed microchannels and precisely controlled external physical separation methods that utilize acoustic fields [ 11 , 12 ], fluorescence activation [ 13 , 14 ], optical filing [ 15 , 16 ], magnetic activation [ 17 , 18 ], and electrical fields [ 19 , 20 , 21 ]. Shamloo et al [ 11 ] simulated the separation of blood cells with acoustic fields, while evaluating the most efficient and low-cost separation devices by altering factors of acoustic field devices.…”
Section: Introductionmentioning
confidence: 99%
“…Shamloo et al [ 11 ] simulated the separation of blood cells with acoustic fields, while evaluating the most efficient and low-cost separation devices by altering factors of acoustic field devices. In addition, Rosental et al [ 14 ] demonstrated and developed a method to isolate different cell populations in corals and other cnidarians using fluorescent activated cell sorting (FACS) technology, which is an advanced cell sorting technique. Further, Tamura et al [ 15 ] used optical cell separation technology to separate and classify heterogeneous cancerous cells based on morphology, confirming the feasibility of optical technology in cancer cell manipulation.…”
Section: Introductionmentioning
confidence: 99%